2021
DOI: 10.1093/biolinnean/blab115
|View full text |Cite
|
Sign up to set email alerts
|

Repeated dietary shifts in elapid snakes (Squamata: Elapidae) revealed by ancestral state reconstruction

Abstract: Identifying the traits of ancestral organisms can reveal patterns and drivers of organismal diversification. Unfortunately, reconstructing complex multistate traits (such as diet) remains challenging. Adopting a ‘reconstruct, then aggregate’ approach in a maximum likelihood framework, we reconstructed ancestral diets for 298 species of elapid snakes. We tested whether different prey types were correlated with one another, tested for one-way contingency between prey type pairs, and examined the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Regardless of phylogenetic relatedness, we found that large‐bodied python species showed an increased preference to consume endotherms, whereas smaller species more frequently use ectotherms. Similar relationships between snake size and endotherm prey utilization have been observed in some species of elapids (Maritz et al., 2021) and in New World lampropeltines (Pyron & Burbrink, 2009). Importantly, all of the larger‐most species of pythons (i.e.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Regardless of phylogenetic relatedness, we found that large‐bodied python species showed an increased preference to consume endotherms, whereas smaller species more frequently use ectotherms. Similar relationships between snake size and endotherm prey utilization have been observed in some species of elapids (Maritz et al., 2021) and in New World lampropeltines (Pyron & Burbrink, 2009). Importantly, all of the larger‐most species of pythons (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Several factors other than body size can influence the evolution of differential prey use by snakes. Notably, ecological opportunity afforded by geographic colonization of novel habitats is among the most influential drivers of the evolution of diet in snakes (Barends & Maritz, 2022a; Greene, 1997; Grundler & Rabosky, 2021; Maritz et al., 2021; Naik et al., 2021). The most recent common ancestor of the pythons likely originated in Asia during the Oligocene before subsequently dispersing through Africa and Oceania respectively (Esquerré et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an exception, D. polylepis is often (but not always) more ground-dwelling than its congeners, being commonly found in open savannas and rocky hills [ 44 , 45 ]. Overall, mambas mainly prey on birds and small mammals such as rodents and bats [ 42 , 46 ], although their diet and ecology are poorly known.…”
Section: Resultsmentioning
confidence: 99%
“…The main task of the ancestral state reconstruction problem is to estimate the trait value of the most recent common ancestor of a group of species from their observed trait values. This problem has many applications in ecology and evolution, such as reconstructing ancestral diets (Maritz et al, 2021), studying female song in songbirds (Odom et al, 2014), and inferring the origin of infectious disease epidemics (Faria et al, 2014;Gill et al, 2017). Moreover, ancestral state reconstruction methods have been applied to reconstruct the place of origin of a language family (Bouckaert et al, 2012;Neureiter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%